Barton decarboxylation under ultrasonic continuous flow. (4th July 2016) - Banaszak-Léonard, Estelle; Mangin, Floriane; Len, Christophe
Abstract : Barton decarboxylation was performed in ultrasonic continuous flow for bulkier syntheses and enhanced yields compared to conventional heating. Abstract : Barton decarboxylation reaction was performed and optimized in an ultrasonic continuous flow. Indeed, continuous flow was chosen to give access to bulkier syntheses, ultrasounds were used to enhance yields compared to simple heating. Various Barton adducts and reductive decarboxylated compounds were obtained in moderate to good yield (33–73%).